Contextual Reflection of Migration Through Textile Art - Fobiri, George Kwame; Howard, Ebenezer Kofi; Badoe, William; Ayesu, Solomon Marfo; Eghan, Benjamin; Kansanba, Rowena Fatchu; Nyarko, Michael Obeng (Journal of Urban Culture Research, 2025)
Controlling migration, especially the irregular type, has been an issue of global concern and one of the contending issues in academic discourse today. The study sought to create a reflection of human migration in the national developmental agenda through textile art. As a qualitative study, the Practice-based research design was adopted. Also, conceptual fabrics in the Ghanaian context were used since they add more meaning to stories with their conceptual nature. With immigrants, immigration officers, and refugee camp officers as a target, a sample size of 15 coupled with 105 engaged in an exhibition was considered. Interviews and Observations were used as instruments to solicit information from the participants. The study reveals the suitability of textile art in story-telling on pressing issues using mixed-media and panel concepts of art creation. It is recommended that artists should pay attention to pressing issues like migration in their creations to ensure national development.